The effects of rosuvastatin and pravastatin on bone metabolism in diabetic rats (Annals of Medical Research, 2021)
Aim: In this study, the effects of rosuvastatin and pravastatin on bone metabolism were evaluated. Comparison of the positive or negative effects of two different statins on biochemical parameters related to bone metabolism in 20 mg / kg / day diabetic rats will be contribute to the enrichment of the literature on this subject. In addition, information will be obtained about whether the use of statins will be beneficial in bone metabolism disorders that may occur due to aging or diabetes in DM patients.Materials and Methods: In a diabetic rat model induced by Streptozotocin (STZ), the possible effects of Rosuvastatin and Pravastatin, both of which are hydrophilic, on biochemical parameters and histologycal examination related to bone metabolism (20 mg / kg) were examined in comparison with the control groups.Results: In the intergroup comparisons, Phosphate (P) level was lower in the Pravastatin group than the controls (P = 0.017). However, there was no difference in the P level in the Rosuvastatin group compared to the control group and the diabetes group. The calcium (Ca) level was increased in the Rosuvastatin group then the the controls (P = 0.002). However, there was no significant change in Ca level in the Pravastatin group. The vitamin D2 level of rats was similar in all groups and was not statistically significant. There was no significant difference between the groups in terms of both osteoblastic activity and bone marrow cellularity.Conclusion: In conclusion, although more extensive studies are needed, our study revealed that the serum Ca level was high in rats given rosuvastatin, and P levels were low in rats given pravastatin. But cytologically, there was no change in bone structure. Our study revealed that we should be a little more cautious about the information that statins have a positive effect on bone tissue.